The genome sequence of the red fox, Vulpes vulpes (Linnaeus, 1758) [version 1; peer review: 2 approved] - Michelle O’Brien; Rosa Lopez Colom (Wellcome Open Research, 2025)
We present a genome assembly from an individual female Vulpes vulpes (red fox; Chordata, Mammalia, Carnivora, Canidae). The assembly comprises two haplotypes, with total lengths of 2,411.71 megabases and 2,398.53 megabases, respectively. For both haplotypes, 97.8% of haplotype 1 and 97.97% of haplotype 2 are scaffolded into 17 chromosomal pseudomolecules. Additionally, the mitochondrial genome has been assembled, with a total length of 16.68 kilobases.